A Note on the Multiplier - Shaw, E. S. (Review of Economic Studies, 1938)
Journal Article A Note on the Multiplier Get access E. S. Shaw E. S. Shaw Stanford, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 60–64, https://doi.org/10.2307/2967539 Published: 01 October 1938